The Guidelines for the Knowledge Management in Koh Rian Sub-district Administrative Organization, Pharnakhon Si Ayutthaya District, Phranakhon Si Ayutthaya Province - Khophet , Benyapha; Anusonphat, Nalaumon (Journal of Human and Society, Sisaket Rajabhat University, 2023)
The objectives of this research were: 1) to study the knowledge management; and 2) to add out the guidelines for the knowledge management in Koh Rian sub-district administrative organization. This study employed mixed methods approach. Data collection in quantitative research was undertaken using a questionnaire. The sample were 53 officers in Koh Rian sub-district administrative organization. Frequency, percentage, mean, and standard deviation were calculated in data analyzing. The in-depth interview was used in qualitative data collection. The interviews were conducted with 8 key informants, selected purposively. The content analysis was used in data analysis. The results of the research were as follows: 1) The knowledge management in Koh Rian sub-district administrative organization in overall was at a high level. The highest average score was found in the knowledge identification; meanwhile, the lowest average score was found in the knowledge organization; and 2) The dimensions were several steps of the knowledge management in Koh Rian sub-district administrative organization. (1) Knowledge identification should be related to the administrative policy, vision, mission and strategy. The vision should be determined by the officers, people, and stakeholders. (2) Knowledge creation and acquisition should be taken through training program, seminar, civil society forum, meeting, as well as internal and external knowledge management activities. (3) Knowledge organization should be systematically arranged, and the knowledge content should be developed to create information system. (4) Knowledge codification and refinement should be proceeded by the administrator. The information should be updated and convenient. (5) Knowledge access should be flexible to be widely available. (6) Knowledge sharing should be collaborative. The mentoring should provide the comfortable learning atmosphere and the information should be published in online database; (7) Knowledge learning should be operated in ways that can solve related problems to achieve the mission, and lead to an innovation.